Higher Education Institutions and Post-Covid In-Demand Employability Skills: Responding Through Curriculum that Works - Samuel O. Babalola; Clement O. O. Kolawole (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
This study explained that the post-Covid world of work would demand a new set of employability skills. Higher education institutions need to respond by preparing graduates with manifest post-COVID-19 employability skills through innovatively delivered curricula. Through literature review, the study identified post-Covid-19 in-demands employability skills and ways of innovatively fostering them. The study adopted the descriptive survey method and canvassed (104) faculty members’ (from 9 public universities) opinions through an online poll on the skills they considered relevant for post-pandemic graduate employability and integrating them into universities curricula. Data collected were descriptively analyzed using frequency count and percentage. Findings showed that when universities commit to innovative curriculum delivery, students can easily acquire skills and competencies required to effective security and create jobs in the post-Covid job market effectively recommended that universities should innovate their curricula by integrating post-Covid in-demands skills needed for students’ post-Covid job market.